1985
DOI: 10.1111/j.2042-7158.1985.tb05063.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the potency of 8−phenyltheophylline as an antagonist at A1 and A2 adenosine receptors in atria and aorta from the guinea-pig

Abstract: The potency of 8-phenyltheophylline as an antagonist at A1 adenosine receptors in guinea-pig atria and at A2 adenosine receptors in the guinea-pig aorta has been investigated. 8-Phenyltheophylline was an apparently competitive antagonist of the negative chronotropic effect of adenosine, 2-chloroadenosine, L-N6-phenyl-isopropyl adenosine (L-PIA) and 5'-N-ethylcarboxamide adenosine (NECA) on atria and of the relaxant effect of adenosine, 2-chloroadenosine and NECA on the aorta. The pA2 values for 8-phenyltheophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 10 publications
4
24
0
Order By: Relevance
“…This dual action could potentially result in a disinhibition of the effects of endogenous adenosine and the erroneous conclusion that adenosine is not involved in a response. 8-Phenyltheophylline (adenosine receptor PA2 of 6-4; Collis, Palmer & Saville, 1985) lacks any action of phosphodiesterase activity (Smellie, Davis, Daly & Wells, 1979). We have previously also shown that the present infusion rate 8-phenyltheophylline used is sufficient to produce an approximate 100-fold rightward shift in the vasodilator dose-response curve to adenosine (Collis & Nowell, 1986).…”
Section: Discussionmentioning
confidence: 82%
“…This dual action could potentially result in a disinhibition of the effects of endogenous adenosine and the erroneous conclusion that adenosine is not involved in a response. 8-Phenyltheophylline (adenosine receptor PA2 of 6-4; Collis, Palmer & Saville, 1985) lacks any action of phosphodiesterase activity (Smellie, Davis, Daly & Wells, 1979). We have previously also shown that the present infusion rate 8-phenyltheophylline used is sufficient to produce an approximate 100-fold rightward shift in the vasodilator dose-response curve to adenosine (Collis & Nowell, 1986).…”
Section: Discussionmentioning
confidence: 82%
“…The interaction of PACPX with the non-selective adenosine receptor antagonist 8-phenyltheophylline (8-PT; Collis et al, 1985) was determined to ascertain whether the two xanthines acted at a common site. A control concentration-response curve was generated to 2-chloroadenosine and was repeated after exposure for 1 h to either PACPX (1OgIM) or 8-PT (1OI1M).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with the non-selective adenosine receptor antagonist, 8-PT (Collis et al, 1985) yielded interesting results in RCMM. 8-PT produced concentration-dependent rightward shifts of the NECA curves with CR values consistent with adenosine-receptor antagonism (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…8-PT produced concentration-dependent rightward shifts of the NECA curves with CR values consistent with adenosine-receptor antagonism (i.e. pKB 6.4-6.6, Collis et al, 1985 which 8-PT enhanced the contraction to NECA in RCMM remains to be determined.…”
Section: Discussionmentioning
confidence: 99%